Social Inequality in Single Parent Family Resilience Programs: A KAP Analysis ​ - Novianti, Herny; -, Ilfiandra; Riksa Yustiana, Yusi; Hayati Dahlan, Tina (Universitas Islam Negeri Raden Intan Lampung, 2026)
Family resilience programs are intended to support families facing psychosocial and structural challenges. However, limited studies have examined how policy interpretations and everyday guidance practices reproduce social inequality within programs for single parentfamilies. This study explores these dynamics using a qualitative Knowledge–Attitude–Practice (KAP) framework. A qualitative descriptive design was employed involving 59 purposively selected informants, including policy stakeholders, Motekar facilitators, community cadres, single parents, and children from single parenthouseholds. Data were collected through in-depth interviews and document analysis and analyzed thematically across KAP dimensions. The findings reveal a persistent policy–practice–experience misalignment. Policy actors tended to frame family resilience through administrative perspectives that were weakly connected to families’ lived realities, while guidance practices remained standardized and insufficiently responsive to psychosocial vulnerability and everyday survival challenges. This study contributes to family resilience research by demonstrating how social inequality is reproduced through misaligned knowledge, attitudes, and practices within community-based interventions. The findings emphasize the need for more context-sensitive and relational approaches that meaningfully incorporate the experiences of single parentfamilies and children.